Therapeutic Strategies for Dry Mouth Management with Emphasis on Electrostimulation as a Treatment Option - Amela Tulek; Aida Mulic; Martine Hogset; Tor Paaske Utheim; Amer Sehic (Hindawi Limited, 2021)
Objectives. Xerostomia is a subjective sensation of dry mouth. It is commonly associated with salivary gland hypofunction. Both changes in the composition of the saliva and a reduction in the quantity secreted may be an objective finding of dry mouth. Although there are no currently available cures for the conditions resulting in dry mouth, there are several treatment options that give hope for patients who suffer from xerostomia. Individuals with some residual salivary gland function, which are contraindicated to pharmacological therapies, would benefit the most from identifying novel, alternative effective methods for stimulating production of saliva. The aim of this study was to give an overview of the latest and most relevant data related to treatment modalities for the management of dry mouth conditions. Data Resources and Study Selection. The present review was prepared by searching the National Library of Medicine database using the relevant medical terms and their combinations. A total of thirty-three studies met the inclusion criteria. Data were extracted by one author and verified by another. Conclusion. A number of patients showed positive treatment outcomes, and the adverse effects of both electrical stimulation (ES) and acupuncture have been reported as mild and transient. In patients who have undergone radiotherapy, acupuncture is shown to increase salivation. However, in patients with Sjogren's syndrome, the effects of ES devices seem to be elusive. Moreover, due to the instability of the findings in relation to longevity of clinical effect, patient satisfaction, quality of life, and clinical effectiveness of such treatments, the results remain vague.